Redox-dependent protein S-glutathionylation governs azacitidine sensitivity and resistance in AML - Nemes, Dušan; Myšáková, Michaela; Minařík, Lubomír; Jonášová, Anna; Stopka, Tomáš; Pimková, Kristýna Gloc (Redox biology, 2026)
Disruption of redox metabolism is a hallmark of drug-resistant cancer cells, representing a major obstacle to the effective treatment of acute myeloid leukemia (AML). While recent studies have highlighted the importance of redox balance in AML therapy, the specific contribution of protein redox signaling to resistance remains poorly understood. Defining these mechanisms could uncover therapeutic vulnerabilities of resistant AML cells and guide the development of novel combination strategies. Here, we performed comprehensive mass spectrometry-based redox and quantitative proteomic profiling of AML cell lines and patient samples sensitive or resistant to the hypomethylating agent azacitidine (AZA). We demonstrate that AZA disrupts redox homeostasis, which inactivates the glyoxalase system and DNA damage response, and thereby induces cell death. In contrast, AZA resistance is associated with a redox reset characterized by elevated glutathione levels and diminished protein S-glutathionylation. Importantly, AZA failed to induce oxidation of proteins in these pathways in resistant cells and patient-derived AML samples. Pharmacological inhibition of glutathione synthesis restored protein S-glutathionylation and resensitized resistant AML cells to AZA.
Keywords: Redox proteomics; Proteomics; protinádorové antimetabolity; azacytidin; Cell Line, Tumor; Cysteine oxidation; Azacitidine; Oxidation-Reduction; glutathion; Humans; akutní myeloidní leukemie; proteomika; Glutathione; Drug Resistance, Neoplasm; Drug resistance; poškození DNA; DNA Damage; oxidace-redukce; Leukemia, Myeloid, Acute; nádorové buněčné linie; Hypomethylation therapy; lidé; chemorezistence; Glyoxalase system; S-glutathionylation; Acute myeloid leukemia; DNA damage; Antimetabolites, Antineoplastic